Influência do histórico familiar de hipertensão e o polimorfismo do gene da enzima conversora da angiotensina (RS1799752) na modulação autonômica cardíaca em adolescentes - DIAS FILHO, Carlos Alberto Alves (2018)
Introduction: Systemic arterial hypertension is a chronic-degenerative disease with multifactorial origin and characterized by elevated and sustained levels of blood pressure (BP), increasing risk for cardiovascular diseases. Some environmental and genetic factors have a strong impact on the prevalence of this morbidity. Besides these factors, exist the autonomic imbalance. The autonomic imbalance is recognized as one of the main causes of systemic arterial hypertension. However, few studies have explored the impact of the presence of angiotensin converting enzyme gene polymorphism and family history of hypertension on autonomic dysfunction in adolescents. Aim: To analyze the autonomic modulation of adolescents with family history of hypertension and the participation of the angiotensin converting enzyme gene polymorphism. Materials and Methods: The sample consisted of 141 adolescents with mean ages of 14.89 ± 1,64 years, students of a public schools of São Luís, Maranhão. The students were divided in offspring of hypertensive parents group (OHP) and offspring normotensive parents group (ONP). Then, an electrocardiogram for posterior analysis of heart rate variability was performed, blood pressure collects, anthropometric measures, oral mucosal cells collect, and posteriorly genotyping and statistical analysis. Results: The main finding of this study was the reduction of vagal action in the OHP group in relation to the ONP group, both presenting the DD genotype. The results showed changes in the variables: Weight (kg): 52.07 ± 9.38 vs. 58.35 ± 10 , 53; BMI (kg / m²): 20.01 ± 2.76 vs. 22.34 ± 4.30; WC (cm): 67.44 ± 6.94 vs. 72.01 ± 8.18; HR (bpm): 78.90 ± 12.73 vs. 84.84 ± 9.99; Var RR (ms²): 2408 ± 212 vs. 1182 ± 819; | LF (ms²): 1463 ± 1448 Vs. 802 ± 851; LF (%): 43 ± 16 vs. 54 ± 16; HF (%): 57 ± 16 vs. 46 ± 16; RMSSD (ms): 51 ± 26 Vs. 40 ± 20 and SD1 (ms): 39 ± 21 vs. 29 ± 14. Differences were also found when compared only the groups FPH vs. FPN on the variables %fat (%): 23.60 ± 8.33 vs. 26.33 ± 7.08; SBP (mmHg): 109.22 ± 11.32 vs. 114.62 ± 11.49; HR (bpm): 78.92 ± 12.85 vs. 83.53 ± 12.30; LF (%): 43.63 ± 15.25 vs. 48.60 ± 17.14; HF (%): 57.36 ± 15.25. Significant differences were also found when divided FPH DD + DI vs. FPN DD + DI in BMI (kg / cm²): 20.30 ± 3.35 vs. 22.05 ± 4.23; SBP (mmHg): 109.52 ± 11.49 vs. 114.54 ± 11.35; LF (%): 43.66 ± 15.90 vs. 50.49 ± 17.38 and HF (%): 56.33 ± 15.90 vs. 49.47 ± 17.37. Conclusion: Adolescents with DD genotype and family history of arterial hypertension present minor cardiac autonomic modulation as a predictive factor of pathophysiological changes of the disease.